(untitled) (Medicine Today, 2023)
Introduction: Irritable bowel syndrome is a common chronic functional gastrointestinal disorder characterized by abdominal pain associated with altered bowel habit of either diarrhoea, constipation or both. Its pathogenesis is multifactorial and incompletely understood.The role of gut microbiota in the pathophysiology of IBS is supported by various evidences.These are differences in mucosal and faecal microbiota between patients with IBS and healthy individuals,development of post-infectious IBS and the efficacy of some probiotics and nonsystemic antibiotics such as Rifaximin. Previous study showed resetting microbial diversity via Rifaximin use may lead to a decrease in bacterial fermentation and a reduction in the clinical symptoms of IBS. This study is designed to assess efficacy of Rifaximin in diarrhoea predominant irritable bowel syndrome. Objective: This study was conducted to assess the effectiveness of Rifaximin in diarrhoea predominant irritable bowel syndrome patient. Materials and Methods: This quasi experimental study was conducted on patients aged 18-55 years with IBS-D in department of Gastroenterology, BSMMU during the period of September, 2020 to August, 2021. Results: There was significant improvement on abdominal pain(p <0.001), abdominal bloating(p =0.001) and satisfaction with bowel movement( p<0.001) in Rifaximin group at 4th week from baseline and most of which sustained upto 12th week of study. The total IBS-SSS at baseline (328.7 ±13.7) decreased to (231.5±14.2) at 12th week of study in Rifaximin group which was significant (p <o.oo1). In placebo group IBS-SSS also gradually decreased from baseline (323.4±17.29) to 12th week (269.3±16.2) but statistically not significant. IBS-QOL score at baseline in Rifaximin group was 64±5.2 and in placebo group was 63.4±5.1. Total IBS-QOL score was increased with time in both Rifaximin and placebo group but none was significant. Conclusion: Rifaximin was more effective than placebo in controlling abdominal pain, abdominal bloating and dissatisfaction with bowel movement after 12th week of study. IBS QOL score was also increased in both groups. Medicine Today 2023 Vol.35(1): 44-48